HYDROGEOLOGICAL CONCEPTUAL MODEL NIMBOYORES AQUIFER, GUANACASTE, COSTA RICA - García, Mario A. (2011)
The Nimboyores aquifer, located in the province of Guanacaste (Costa Rica) has been defined in thiswork as an unconfined aquifer, it is composed of three layers: the deepest one is a thick colluvium, the intermediate isa thin colluvium and at the top there is a sandy clay soil. The basement depth varies between 30 and 45 m. This modelwas obtained by correlating the results of 7 vertical electrical soundings with 50 wells with lithological informationprovided by the SENARA. The hydraulic conductivities of such layers are respectively 300, 60 and 10 m/d. The totalrecharge to the aquifer is of 1211 l/s, obtained from the water balance. Based on the record levels in 14 wells collectedduring 7 years monitored by SENARA, static levels were established for the driest month recorded. The conceptualmodel improved the understanding of the groundwater flow and the influence of the geological setting.